Efektivitas Kerja Pemerintah Kota Manado dalam Program Bantuan Korban Banjir di Kecamatan Wanea Kota Manado - Timban, Christian David; Mandey, Jantje; Tulusan, Femmy (Sam Ratulangi University, 2015)
Catastrophic floods which occurred in the town of manado on 15 January 2014 to date is one of the largest floodsever to occur in North Sulawesi manado city in particular. And the Government of the city of manado in the disaster reliefespecially in aid disaster victims have good planning but have not been effective in its application to see there are stillmany citizens of disaster victims who are still living and settled in the disaster site with circumstances that could not besaid to be as good as before they suffered a disaster, because of the uneven in its application to all disaster victims indistrict wanea.In this study uses qualitative methods to describe conditions that actually happened in a field supported byinterviews to the informant-informant, observations of direct, search documents – documents and documentation. Thefocus of this research was to determine the effectiveness of government aid programs in manado city wanea from programplanning, quality of service/program, the organizers of the program and satisfaction. The results showed that in generalthe overall results of interviews about the effectiveness of the work of the Government of the city of manado in aid floodvictims in district wanea manado City gives the conclusion that the aid program for flood victims in wanea district of thecity of manado is quite good but not yet effective.Key words: effectiveness of work Programs help flood victims